“It helps me get closer to their writing experience” Classroom ethnography and the role of technology in third-year FL courses - Gleason, Jesse (System, 2014)
Research has shown a disjunction between language instruction at the lower and upper levels of foreign language (FL) study. Whereas lower-division courses focus on grammatical patterns, upper-level courses focus on specific content. The third-year writing course is in a unique position to help learners prepare for the types of learning that they will encounter in more advanced language use contexts. Using grounded classroom ethnography, this multiple case study of two classrooms chronicles how a collaborative partnership between an instructor and an applied linguist facilitated the integration of two types of technology into a third-year Spanish writing course at a North American University. Technology was carefully chosen based on pedagogical considerations and teacher goals. Students in these courses included a mixture of heritage and FL Spanish learners with a mean age of 21 years. Findings included four ways that technology played a role in third-year Spanish language learning, including as: (a) a way to alleviate their workloads, (b) a motivator, (c) a way to improve the quality and quantity of feedback students received in the course, and in some cases (d) antagonistic to language learning. Implications of classroom ethnography for research on blended learning are drawn. Published by Elsevier Ltd.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000345155800012, lens.org/016-859-492-698-057 tex.type: [object Object]
Keywords: Blended language learning; Discourse analysis; Ethnography; Language-content gap; Spanish; Teacher-researcher collaboration; Technology; Third-year FL courses; Writing; dept.wll

Meaning-based scoring: A systemic functional linguistics model for automated test tasks - Gleason, Jesse (Hispania-a Journal Devoted to the Teaching of Spanish and Portuguese, 2014)
Communicative approaches to language teaching that emphasize the importance of speaking (e.g., task-based language teaching) require innovative and evidence-based means of assessing oral language. Nonetheless, research has yet to produce an adequate assessment model for oral language (Chun 2006; Downey et al. 2008). Limited by automatic speech recognition (ASR) technology, which compares non-native speaker discourse to native-like discourse, most tests exclusively focus on accuracy while ignoring how examinees use language to make meaning. In order to offer stakeholders more trustworthy evidence of how examinees might use language in target language domains, a model anchored in systemic functional linguistics (SFL) is put forth. Specific examples are given of how SFL might be used to evaluate test task types, such as the story retell:three examinees' responses are contrasted using genre analysis (Derewianka 1990) and transitivity analysis (Ravelli 2000) in order to demonstrate elements in their linguistic profiles that ASR-based assessment would overlook. In so doing, implications are drawn regarding the potential of SFL models for enhancing automated scoring procedures by focusing on the meaning-form relations in the linguistic construction of narrative.
7 citations (Crossref) [2023-10-31] tex.eissn: 2153-6414 tex.unique-id: ISI:000345494100012
Keywords: Adult Spanish literacy alfabetización adulta de español; Automated language assessment evaluación automática del lenguaje; Discourse analysis análisis del discurso; Systemic functional linguistics lingüística sistémico-funcional; Transitivity analysis análisis de transitividad; dept.wll; peer-reviewed

Patterns of tasks, patterns of talk: L2 literacy building in university Spanish classes - Gleason, Jesse; Slater, Tammy (Language, Culture and Curriculum, 2017)
Second language (L2) classroom research has sought to shed light on the processes and practices that develop L2 learners' abilities [Nunan, D. 2004. Task-based language teaching. London: Continuum; Verplaetse, L. 2014. Using big questions to apprentice students into language-rich classroom practices. TESOL Quarterly, 179, 632-641; Zeungler, J., & Mori, J. 2002. Microanalyses of classroom discourse: A critical consideration of method. Applied Linguistics, 23(3), 283-288]. Honing in on the micro-level of classroom tasks and even further into the language of the tasks can help to reveal the patterns in teacher- and student-talk that help scaffold students' academic literacy. Literacy, from a systemic functional view of language learning, entails having the tools to function in the social contexts that are valued in students' lives. This study illustrates how grounded ethnography was used in conjunction with functional discourse analysis to illuminate bi-literacy development in two third-year university Spanish writing classes. Findings uncovered unique patterns of tasks and oral interactions that helped build students' academic bi-literacy. While grammar tasks helped build students' knowledge of wording-meaning relationships, culture and writing tasks supported their evolving understanding of how language construes content. This study puts forth a systemic functional curricular model for literacy-based tasks that aims to bridge the previously observed language-content gap.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-343-356-989-268, pop00144 tex.type: [object Object]
Keywords: Language learning tasks; academic literacy; blended learning; classroom discourse; dept.wll; systemic functional linguistics; third-year Spanish courses

Promoting social justice with CALL - Gleason, Jesse; Suvorov, Ruslan (CALICO Journal, 2018)
11 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-216-002-732-944, pop00223 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed

The knowledge framework for building teacher awareness of language in content instruction - Schmitt, Elena; Gleason, Jesse (Social Practices in Higher Education; A Knowledge Framework Approach to Linguistic Research and Teaching; Slater, 2023)
Keywords: dept.wll

Challenges and achievements of an online intercultural exchange in time of crisis - Fornara, F; Gleason, Jesse (How We Take Action: Social Justice in PK-16 Language Classrooms, 2023)
How We Take Action brings together practical examples of social justice in language education from a wide range of contexts. Many language teachers have a desire to teach in justice-oriented ways, but perhaps also feel frustration at how hard it is to teach in ways that we did not experience ourselves as learners and have not observed as colleagues. As a profession, we need more ideas, more examples, and wider networks of allies in this work. This book includes the work of 59 different authors including teachers and researchers at every level from Pre-K to postsecondary, representing different backgrounds, languages, and approaches to classroom practice. Organized into three sections, some of the chapters in this collection report on classroom research while others focus on key practices and experiences. Section I is entitled Inclusive and Empowering Classrooms. In this section authors take a critical approach to classroom practices by breaking with the status quo or creating spaces where students experience safety, access, and empowerment in language learning experiences. Section II, Integration of Critical Topics, addresses a variety of ways teachers can incorporate justice-oriented pedagogies in day-to-day instructional experiences. Social justice does not happen haphazardly; it requires careful, critical examination of instructional practices and intentional planning as instructors hope to enact change. Section III, Activism and Community Engagement, explores how teachers can empower students to become agents for positive change through the study of activism and constructive community engagement programs at local and global levels.
Keywords: dept.wll

The knowledge framework for building teacher awareness of language in content instruction - Gleason, Jesse; Schmitt, Elena (Social practices in higher education - A knowledge framework approach to linguistic research and teaching, 2021)
Keywords: dept.wll; faculty_collection

Patterns of oral choice and evaluation across secondary content areas. - Gleason, Jesse; Berg, Margaret A; Huang, Jingzi (Language and Education, 2018)
Our study focuses on Choice and Evaluation, two of Mohan's knowledge structures to uncover how teachers and students across content areas developed disciplinary knowledge through classroom talk. Participants included in-service teachers and their students in rural and urban secondary schools in the Eastern and Western US. Through Choice and Evaluation, we examined opportunities for students across four disciplines to build up their knowledge of content matter or field. Findings revealed that teachers of math and science built students' field knowledge through classroom exploration, eliciting Evaluation in dialogic patterns involving Choice, while social studies and language arts teachers helped students implicitly use Choice/Evaluation through projects based on their previous experiences. The essential role of student background knowledge in enabling participation across different types of oral exchanges is shown. This study uncovers tendencies across classrooms and makes linguistically informed suggestions for teachers in the disciplines.
0 citations (Crossref) [2023-10-31] Citation Key Alias: gleasonPatternsOralChoice2018, lens.org/109-314-805-638-437 tex.type: [object Object]
Keywords: Teacher education; classroom discourse; dept.wll; language across content; peer-reviewed